2017
DOI: 10.1002/adom.201600917
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processing Small‐Molecule Organic Emitter in Field‐Induced, Carrier Gated Lighting Devices

Abstract: polymers, organic small molecule materials provide more advantages, particularly high stability and a wide selection of emitter materials which span the entire visible spectrum. [17,18] The major drawback of organic small molecule thin film devices is the considerably strict manufacturing requirement on high vacuum evaporation. [19] Therefore, it is necessary to develop an alternating current organic electroluminescent (AC-OEL) device based on soluble organic small molecule emitters.Due to the insulators sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Since the utilization of inorganic ZnO‐gate is beneficial to reduce overheating caused by excessive hot carriers at the interfaces, Xu et al further explored tris(8‐hydroxyquinoline) aluminum (Alq 3 ) with adequate solubility as the emitters in AC‐driven organic EL devices, as shown in the inset of Figure a . The performance of the solution‐processed Alq 3 ‐based AC‐driven organic EL devices with a gate layer of ZnO for which the chloroform, acetone, and dimethyl formamide (DMF) were utilized for the dissolution of Alq 3 were investigated and compared.…”
Section: Optimizing Strategies For Ac‐driven El Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the utilization of inorganic ZnO‐gate is beneficial to reduce overheating caused by excessive hot carriers at the interfaces, Xu et al further explored tris(8‐hydroxyquinoline) aluminum (Alq 3 ) with adequate solubility as the emitters in AC‐driven organic EL devices, as shown in the inset of Figure a . The performance of the solution‐processed Alq 3 ‐based AC‐driven organic EL devices with a gate layer of ZnO for which the chloroform, acetone, and dimethyl formamide (DMF) were utilized for the dissolution of Alq 3 were investigated and compared.…”
Section: Optimizing Strategies For Ac‐driven El Devicesmentioning
confidence: 99%
“…So far, researchers have been carrying out the arduous work in simplifying the fabrication technology, optimizing the device configuration, upgrading the dielectric layers, exploiting new electrodes types and emitting nanomaterials, resulting in many inspiring advancements . However, surprisingly, there are few comprehensive review articles focusing on the flourishing development of AC‐driven EL devices, aside from one progress report involving AC‐driven OLEDs .…”
Section: Introductionmentioning
confidence: 99%
“…[48] The light emission in AC-LEDs relies on the recombination and formation of excitons in the emitting layer; it can be concluded that the performance of an AC-driven device with the luminescence mechanism based on charge recombination depends on the formation of excitons in the emitting layer under an AC electric field. [61,62] Excitons may be generated by injecting one type of charge from the external electrode or through the frequent creation of field-induced charges within the device under a cycle of alternating voltages. Hence, the device performance of AC-driven devices with the luminescence mechanism of charge recombination depends on the impactful injection of charges with the exciton generation and charge recombination balance between the electrons and holes under the AC electric field.…”
Section: Exciton Recombination Mechanismmentioning
confidence: 99%
“…It has recently been shown that AC‐OEL devices gated by n‐type wide band gap semiconducting layers in place of the insulator layers, exhibit greater carrier manipulation and luminescent performance advantages in AC power cycles . The “model” for this improvement is rather straightforward.…”
Section: Introductionmentioning
confidence: 99%